REFRAMING MOTHERHOOD IN CONTEMPORARY BOLLYWOOD: A FEMINIST ANALYSIS OF VISUAL NARRATIVES - T, Parvathi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Motherhood has historically served as a critical locus for patriarchal control, functioning as a mechanism through which women’s bodies and subjectivities are colonized. The cinematic apparatus, through its language and imagery, has often perpetuated this patriarchal logic, reinforcing heteronormative and idealized conceptions of motherhood. Visual media frequently participates in the dissemination of cultural propaganda that ensnares mothers within normative frameworks of self-sacrifice, devotion, and moral superiority. However, contemporary Bollywood has witnessed a paradigm shift wherein certain visual narratives challenge these entrenched ideologies by offering mothers greater voice, enhanced visibility, and distinctive identities. This shift has facilitated the emergence of maternal figures who transcend traditional paradigms and actively negotiate patriarchal power structures.